2013
DOI: 10.3892/ijo.2013.1960
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA methyltransferases, histone deacetylases and lysine-specific demethylase-1 suppresses the tumorigenicity of the ovarian cancer ascites cell line SKOV3

Abstract: Abstract. Ovarian cancer is one of the most lethal female malignancies and epigenetic abnormalities are thought to play a vital role in the pathogenesis, development and progression of ovarian cancer. Our goal was to investigate whether the combination of trichostatin A (TSA) and 5-aza-2'-deoxycytidine (decitabine) was superior to single agent on tumorigenicity of ovarian cancer cells. We found that tumorigenicity and metastasis of SKOV3 cells were significantly suppressed by the combination of TSA and decitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Recent reports indicate tumorigenicity and metastasis of ovarian cancer cells is significantly suppressed by the combination of HDAC inhibitor TSA and 5-Aza-dC in xenograft mouse models [78]. Thus, we determined the effects of a combination of TSA and 5-Aza-dC treatments on RGS10 expression and cell viability in chemoresistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…Recent reports indicate tumorigenicity and metastasis of ovarian cancer cells is significantly suppressed by the combination of HDAC inhibitor TSA and 5-Aza-dC in xenograft mouse models [78]. Thus, we determined the effects of a combination of TSA and 5-Aza-dC treatments on RGS10 expression and cell viability in chemoresistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…5-azacytidine and its deoxy derivative 5-aza-2′ deoxycytidine are two FDA approved drugs used in the treatment of AML [43]. Along with the role of these drugs blocking cell proliferation in vitro and in vivo , several studies have suggested a potential role for these drugs in suppressing the metastatic phenotype [44; 45; 46; 47]. For example, Aza has been reported to inhibit invasiveness of human breast, ovarian and non-small lung cancer cell lines [48; 49].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, LSD1 inhibition by HCI-2509 might be applied in combined therapeutical strategies of tumor treatment. Indeed, LSD1 inhibition was recently combined with HDAC and EZH2 inhibitors in treatment strategies in acute myeloid leukemia and glioblastoma, as well as in breast and ovarian cancer (Duan et al, 2017;Huang et al, 2012;Meng et al, 2013;Singh et al, 2011;Wen et al, 2018). However, the treatment approaches in which LSD1 inhibition by HCI-2509 could be combined with chemotherapeutical agents that induce apoptosis and tumor recession indicate innovative promising concepts.…”
Section: Discussionmentioning
confidence: 99%